Randomized open‐label crossover assessment of Prograf vs Advagraf on immunosuppressant pharmacokinetics and pharmacodynamics in simultaneous pancreas‐kidney patients. Issue 2 (29th January 2018) - Cattral, Mark; Luke, Sean; Knauer, Michael J.; Norgate, Andrea; Schiff, Jeffrey; Muirhead, Norman; Luke, Patrick P.
Abstract: Introduction: We assessed the pharmacokinetic and pharmacodynamic impact of converting stable simultaneous pancreas‐kidney (SPK) recipients from standard tacrolimus (Prograf) to long‐acting tacrolimus (Advagraf). Methods: In a randomized prospective crossover study, stable SPK recipients on Prograf were assigned to Prograf with 1:1 conversion to Advagraf or vice versa. Demographics, tacrolimus, mycophenolic acid levels, and Cylex CD4 + ATP levels were taken at specified intervals in addition to standard blood work. Results: Twenty‐one patients, who were a minimum of 1 year post‐transplant, were entered into the study. No difference in tacrolimus or mycophenolic acid levels was noted between patients who were first assigned to Prograf or Advagraf. Additionally, Cylex levels as well as serum creatinine, lipase, and blood sugar levels were unchanged. There were no episodes of rejection during the 6‐month study. Conclusions: It is safe to convert between Prograf and Advagraf 1:1, without major impact on pharmacokinetics or pharmacodynamics in SPK recipients.